Gut microbiota in stunting children: literature review - Putu Nita Cahyawati; I Nengah Sujaya (Bali Anatomy Journal, 2021)
Background: Stunting is one of the chronic nutritional problems experienced by children around the world. Indonesia currently occupies the top three countries with the highest prevalence of stunting in Southeast Asia. Children who suffer stunting are generally more susceptible to disease and are at risk of developing degenerative diseases. Stunting does not only affect health but can also affect the level of intelligence of children. Review: There was an association between stunting and components of the gastrointestinal microbiota (gut microbiota). The gut microbiota in each child is different. It was influenced by various factors such as age, food consumed, and location of residence. Nutritional status, history of recurrent infections, and chronic inflammation of the intestine play an important role in the differences in gut microbiota in stunting children compared to normal children. Conclusion: Although it was known that there is a link between stunting and the components of the gut microbiota, the exact mechanism still needs further research.